2017
DOI: 10.1038/s41598-017-05422-w
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Vitamin E Uptake During Development Impairs Neural Tube Closure in Mice Lacking Lipoprotein Receptor SR-BI

Abstract: SR-BI is the main receptor for high density lipoproteins (HDL) and mediates the bidirectional transport of lipids, such as cholesterol and vitamin E, between these particles and cells. During early development, SR-BI is expressed in extraembryonic tissueScavenger Receptor Class B type I (SR-BI) is the main receptor for high density lipoproteins (HDL), and numerous studies have described its role in mediating the bidirectional transport of lipids between these lipoproteins and cells 1 . In the liver, SR-BI is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 68 publications
0
20
0
Order By: Relevance
“…Indeed, previous work showed that vitamin E feeding at the same dose used in our study (2000 I.U. α-tocopherol/kg diet) in female SR-B1 +/− mice increased lipoprotein vitamin E levels [ 39 ]. Further analysis of vitamin E content in HDL particles should be performed in vitamin E supplemented atherogenic diet-fed SR-B1 KO/ApoER61h/h mice to address this issue.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, previous work showed that vitamin E feeding at the same dose used in our study (2000 I.U. α-tocopherol/kg diet) in female SR-B1 +/− mice increased lipoprotein vitamin E levels [ 39 ]. Further analysis of vitamin E content in HDL particles should be performed in vitamin E supplemented atherogenic diet-fed SR-B1 KO/ApoER61h/h mice to address this issue.…”
Section: Discussionmentioning
confidence: 73%
“…It has been suggested that hyperthermia increases the free radicals formation (24), which results in cardiomyocyte fibrosis (25). However, regarding the preventive effects of vitamin E against ROS and lipid peroxidation (8), the administration of vitamin E in the MDMA + vitamin E group noticeably resulted in testis damage prevention.…”
Section: Discussionmentioning
confidence: 99%
“…As a fat-soluble non-enzymatic antioxidant, vitamin E has antioxidant activity and intercalates lipids in biological membranes. Therefore, vitamin E isomers can stop ROS-based reactions producing lipid peroxides (8). It is reported that vitamin E deficiency impaired the nervous, skeletal, circulatory, muscular, cardiovascular, immune, and reproductive system (9).…”
Section: Mdmamentioning
confidence: 99%
“…Instead, SR-B1 is localized in trophoblast giant cells [ 11 , 13 ] surrounding the entire conceptus, that mediate the first step in maternal-fetal nutrient transport. Consistent with SR-B1 localization in cells mediating nutrient uptake, SR-B1 KO embryos show severe vitamin E deficiency [ 12 ]. Interestingly, maternal dietary supplementation with vitamin E completely rescues the NTD phenotype in KO embryos [ 12 ], underscoring the relevance of this vitamin in neural tube closure in this model.…”
Section: Introductionmentioning
confidence: 87%
“…More recently, we identified the cause of this alteration to be neonatal lethality resultant of neural tube defects (NTD). Between 35 and 50% of SR-B1 KO mouse embryos analyzed in different cohorts failed to close their neural tube in the cranial region, and exhibited exencephaly, a congenital malformation that leads to perinatal death [ 11 , 12 ]. Despite the striking embryonic phenotype observed in SR-B1 KO embryos, SR-B1 protein is not present in the embryo itself during neural tube closure.…”
Section: Introductionmentioning
confidence: 99%